Influence of Store Atmosphere, Taste, Service Quality on Repurchase Decisions Through Satisfaction as Mediation - Sugeng Lubar Prastowo; Bagus Manunggal; Ade Indra Permana (PT. BATARI EDU CALYA, 2024)
This study aims to examine the effects of store ambiance, taste, and service quality on repurchase decisions, with customer satisfaction acting as a mediating variable at Haus! Store located in Dasana Indah, Tangerang City. The research employed a quantitative approach using a causal-associative design. The population consisted of customers of Haus! Store, and the sample was selected using nonprobability sampling through purposive sampling techniques. Data were collected using a structured questionnaire measured on a five-point Likert scale. Data analysis was conducted using descriptive and inferential statistical techniques, applying Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results indicate that store ambiance and taste have a significant partial effect on customer satisfaction, whereas service quality does not significantly influence satisfaction. Furthermore, store ambiance and customer satisfaction have a significant partial effect on repurchase decisions, while taste and service quality do not show a direct significant effect on repurchase decisions. Mediation analysis demonstrates that store ambiance and taste significantly influence repurchase decisions through customer satisfaction as a mediating variable.